$A$ ?

The Gateway to Computer Science Excellence

+1 vote

The sum $\sum_{k=1}^n (-1)^k \:\: {}^nC_k \sum_{j=0}^k (-1)^j \: \: {}^kC_j$ is equal to

- $-1$
- $0$
- $1$
- $2^n$

+1 vote

From the binomial theorem,

$\displaystyle (1+x)^k=\sum_{j=0}^{k} {{}^{k}\textrm{C}_{j}}~x^j$

Putting $x=-1$ to equation above yields,

$\displaystyle (1-1)^k=\sum_{j=0}^{k} {{}^{k}\textrm{C}_{j}}(-1)^j\\ \displaystyle \Rightarrow \sum_{j=0}^{k} (-1)^j~{{}^{k}\textrm{C}_{j}}=0$

Now

$\displaystyle \sum_{k=1}^{n}(-1)^k~{{}^{n}\textrm{C}_{k}} \sum_{j=0}^{k} (-1)^j~{{}^{k}\textrm{C}_{j}}=\sum_{k=1}^{n}(-1)^k~{{}^{n}\textrm{C}_{k}} \times 0=0$

So the correct answer is **B**.

52,345 questions

60,501 answers

201,871 comments

95,325 users